Sensitivity of global terrestrial ecosystems to climate variability: data and R code - Awr, S (University of Oxford, 2016)
Data and coding scripts for Seddon et al. (2016) Nature (DOI 10.1038/nature16986). We derived monthly time-series of four key terrestrial ecosystem variables at 0.05 degree (~5km) resolution from observations by the MODIS sensor on Terra (AM) for the period February 2010-December 2013 inclusive, and developed a method to identify vegetation sensitivity to climate variability over this period (see Methods in main paper).